THE VALUE OF THE COMPOUND DRUGS FORMOTEROL AND IPRATROPIUM BROMIDE IN COMPLEX TREATMENT OF CHRONIC NONSPECIFIC LUNG DISEASES IN CHILDREN - O.I. Simonova (Вопросы современной педиатрии, 2006)
The complex mechanism of development of bronchoobstructive bronchitis in chronic nonspecific lung diseases in children and its effective therapy with the compound bronchodilator berodual are discussed. Berodual comprises b2-adrenoreceptor agonist — fenoterol and anticholinergic drug — ipatropium bromide, that amplify bronchodilatory action of each other. Indications, contraindication and intake peculiarities are illustrated.Key words: chronic nonspecific lung diseases, bronchoob structive syndrome, bronchodilators, children.